Analisis Penyerapan Tenaga Kerja melalui Ekonomi Digital di Kota Medan (Studi Kasus pada UMKM di Kota Medan) - Septiani, Bella Virnadya; Yafiz, Muhammad; Aslami, Nuri (Medan Resource Center, 2023)
This article aims to determine the influence of Social Media and E-Commerce partially and simultaneously on labor absorption in MSMEs in Medan City. This type of research uses a quantitative approach. Data was collected in this research using observation, questionnaires and literature study. The population in this study was 33,789 MSMEs in Medan City with a sample of 100 respondents. The data analysis technique uses multiple linear regression analysis with the help of SPSS 25 software. The results and analysis of the research show that social media has a positive and significant effect on labor absorption. Then E-commerce has a positive and significant effect on labor absorption. Furthermore, social media and e-commerce simultaneously have a positive and significant effect on labor absorption. So this means that social media and e-commerce can explain the influence of 60.9 percent on labor absorption.